Prevention of Terrorism with a Regulatory Model of Violent-Based Extremism that Leads to Terrorism - Agung Mafazi; Hery Lilik Sudarmanto; Satriyani Cahyo Widayati; Fauziah Hanum (Faculty of Law, University of Merdeka Malang, 2023)
Among the reasons behind the occurrence of criminal acts of terrorism is the existence of radical terrorism, which can then develop into violent-based extremism that ends in terrorism. Understanding beyond the limits of normal based on the justification of acts of violence or threats of violence to support the occurrence of criminal acts of terrorism is referred to as acts of violence-based extremism that lead to terrorism. This is under the definition of violence-based extremism that leads to terrorism in article 1 point 2 of the Presidential Regulation of the Republic of Indonesia Number 7 of 2021 concerning the National Action Plan for the Prevention and Mitigation of Violent-Based Extremism Leading to Terrorism 2020-2024, which states that â€œViolent-Based Extremism Leading to Terrorism are beliefs or actions that use violence or threats of extreme violence intending to support or commit acts of terrorism. The beliefs or actions of these people or groups of people then receive the attention of the State so that efforts can be made to prevent the development of beliefs or actions aimed at supporting terrorism into crimes that can threaten the stability of state security, namely terrorism.How to cite item: Mafazi, Agung, Hery Lilik Sudarmanto, Satriyani Cahyo Widayati, and Fauziah Hanum. â€œPrevention of Terrorism with a Regulatory Model of Violent-Based Extremism that Leads to Terrorism.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023): 126-133.Â DOI: doi.org/10.26905/idjch.v14i2.10814.